2022
DOI: 10.3389/fphar.2021.804615
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Assisted Cisplatin Inhibits Bladder Cancer Cell Survival by Modulating Wnt/β-Catenin Signaling Pathway

Abstract: Magnesium, an essential mineral micronutrient, plays a role in the activation of various transporters and enzymes. The present study aimed to investigate the possibility of applying magnesium to enhance the efficacy of cisplatin which is still ranked as one of the major chemotherapeutic drugs for bladder cancer patients. Results showed that the survival rate and colony formation of bladder cancer cells were reduced by combinatorial treatment with cisplatin and magnesium chloride (MgCl2). The proportion of apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The development of drug resistance in cancer cells cannot be separated from the regulation of the tumor microenvironment, in which the interaction of immune cells, tumor stroma and tumor cells gradually establishes resistance of cancer cells. In the study of overcoming drug resistance in cancer cells, we found that the combination of cisplatin and magnesium chloride (MgCl 2 ) could regulate the Wnt/β-catenin signaling pathway to enhance the cisplatin effect and use exosomes to control ferroptosis was also effectively inhibited cancer ( 240 , 241 ). Targeted drugs are often considered to be efficient therapies for cancer, but unfortunately, targeted therapies are all subject to varying degrees of resistance.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…The development of drug resistance in cancer cells cannot be separated from the regulation of the tumor microenvironment, in which the interaction of immune cells, tumor stroma and tumor cells gradually establishes resistance of cancer cells. In the study of overcoming drug resistance in cancer cells, we found that the combination of cisplatin and magnesium chloride (MgCl 2 ) could regulate the Wnt/β-catenin signaling pathway to enhance the cisplatin effect and use exosomes to control ferroptosis was also effectively inhibited cancer ( 240 , 241 ). Targeted drugs are often considered to be efficient therapies for cancer, but unfortunately, targeted therapies are all subject to varying degrees of resistance.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…In addition, intratumor injection of MgCl 2 was recently proven to enhance cellular immunity by regulating CD8 + T-cell activation and cytotoxicity [ 73 ]. In addition, magnesium supplementation has the potential to combat cisplatin resistance [ 82 ] and to modulate inflammatory factors, such as tumor necrosis factor (TNF-α) [ 83 ].…”
Section: The Application Of Metal Ion-based Antitumor Therapeutics An...mentioning
confidence: 99%
“…Combination therapies could reduce the likelihood of acquired resistance, shorten the duration of treatment and speed up recovery 12,13 . Cisplatin, a platinum‐containing anticancer drug, is a non‐specific modulator of the cell cycle and exhibits a strong anticancer effect by interacting with N 7 ‐guanine and N 3 ‐adenine on cancer cells, damaging the structures on the cell membrane, and inhibiting replication of cancer cells, ultimately leading to cancer cell necroptosis 14–17 . However, cisplatin also causes severe toxicities, including nephrotoxicity, peripheral neuropathy and ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Cisplatin, a platinumcontaining anticancer drug, is a non-specific modulator of the cell cycle and exhibits a strong anticancer effect by interacting with N 7 guanine and N 3 -adenine on cancer cells, damaging the structures on the cell membrane, and inhibiting replication of cancer cells, ultimately leading to cancer cell necroptosis. [14][15][16][17] However, cisplatin also causes severe toxicities, including nephrotoxicity, peripheral neuropathy and ototoxicity. Long-term exposure to cisplatin could cause cancer cells to develop drug resistance.…”
Section: Introductionmentioning
confidence: 99%